The Effect of Balance Exercises on Some Kinematical Variables of High Spiking in Volleyball Players - Sadik, Haitham; Sabea , Ahmed (Journal of Physical Education, 2023)
The research aimed at identifying the effect of special balance exercises using different tools on some kinematical variables of volleyball spikers in the Iraqi league. The researchers hypothesized that these exercises have great effect on the development of spiking. They used the experimental method on (6) volleyball spikers from Al Jaish club season 2021 – 2022. The data was collected and treated using SPSS to conclude that arm balance exercises greatly increased vertical jump rates through developing arms by arm swing exercises. The results also showed positive effect on kinematical variables like hip and ball heights during spiking. The researchers recommended the necessity of using adding tools along with balance tools during training session due to their effect on spiking results. Finally they recommended using these balance exercises during special and general preparation phases and giving them proper time during warm-up due to their integral role on developing the players’ level in the next phase; the main exercises phase.